Assessing the Population Status of a Tree Species Using Distance Sampling: Aquilaria crassna (Thymelaeaceae) in Northern Laos. (19th January 2012) - Jensen Jensen, Anders Anders; Meilby Meilby, Henrik Henrik
Abstract : Lack of reliable and accurate field data affect assessments of population status of tree species, especially tropical taxa with broad distributions. Use of distance sampling techniques may help to overcome the problem. This paper describes a method for estimation of absolute density of a rare tree species with scattered and clumped distribution, using line transect distance sampling. The method was applied to previously harvested populations of Aquilaria crassna Pierre ex H. Lec. (Thymelaeaceae) at four sites in Northern Laos. This species is destructively harvested to yield agarwood, probably the world's most valuable nontimber forest product and categorised as "critically endangered". The average density of felled A. crassna trees at the four sites was 2.2 ha −1, indicating that harvesting has been extensive. However, the estimated densities of living saplings, 10.9 ha −1, small trees (DBH < 10 cm), 10.6 ha −1, and larger trees (DBH ≥ 10 cm), 1.7 ha −1, suggest that populations are not wiped flat. The survey method should stand a good chance of wider use as a tool in management and conservation of a wide range of tree species. Results of the present case study could suggest that the conservation status of A. crassna should be re-categorised.